2018
DOI: 10.1002/pbc.27374
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of nabilone for acute chemotherapy‐induced vomiting prophylaxis in pediatric patients: A multicenter, retrospective review

Abstract: Adverse events associated with nabilone were common but of minor clinical significance. Acute CIV control in children receiving nabilone as a part of their antiemetic regimen was poor. Future work should focus on implementation of guideline-consistent CINV prophylaxis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 16 publications
(44 reference statements)
2
14
0
1
Order By: Relevance
“…1: Laredo and Pondra diapirs (López-Horgue et al, 2010); 2: Poza de la Sal diapir (Quintà et al, 2012); 3: Bakio diapir (Poprawski et al, 2014(Poprawski et al, , 2016; 4: Lasarte sub-basin salt controlled basin (Bodego & Agirrezabala, 2013;Bodego, Iriarte, López-Horgue, & Álvarez, 2018); 5-7: Gaujacq and Ossun diapirs (Canérot et al, 2005); 6: Mauléon basin diapirs (Jammes et al, 2010); 8: Cotiella extensional salt area (McClay et al, 2004); 9: Sopeira and Sant Gervàs diapirs (Saura et al, 2016); 10: Villahermosa del Rio diapir (Canérot, 1991); 11: Parcent diapir (Pedrera et al, 2014); 12: Altea diapir (Pedrera et al, 2014;Martínez del Olmo et al, 2015); 13, 14: Finestrat and Elda diapirs (Martínez del Olmo et al, 2015); 15: Jumilla diapirs (Escosa et al, 2018); 16: Western Betics ; 17, 18: Faro and Albuferia diapirs (Ramos et al, 2016); 19, 20: Santa Cruz and Caldas da Rainha diapirs (Alves et al, 2003;Pena do Reis et al, 2017). Iberian Range AB: Aragoneses Branch; Iberian Range CB: Castillan Branch; PB: Parentis Basin; AB: Asturian Basin; AP: As Pontes Basin; ALZ: Asturoccidental-Leonese Zone; CZ: Cantabric Zone; CM: Cantabrian Mountain; CS: Central System; CCR: Catalan Coastal Range; GB: Guadalquivir Basin unconformities within the Jurassic and Lower Cretaceous successions were traditionally interpreted in terms of syn-rift to post-rift differential subsidence between fault-bounded tectonic domains (Aurell et al, 1992;Campos, Aurell, & Casas, 1996;Guimerà, 1988;Liesa, Soria, Meléndez, & Meléndez, 2006;Roca & Guimerà, 1992;Roca, Guimerà, & Salas, 1994;. The only previously documented examples of halokinesis within the Maestrat Basin are a diapir located in the Penyagolosa block near Villahermosa del Río village and in Lucena del Cid, north of Castelló (Canérot, 1989(Canérot, , 1991Trell, Canérot, & Martín, 1979) (see location in…”
mentioning
confidence: 99%
“…1: Laredo and Pondra diapirs (López-Horgue et al, 2010); 2: Poza de la Sal diapir (Quintà et al, 2012); 3: Bakio diapir (Poprawski et al, 2014(Poprawski et al, , 2016; 4: Lasarte sub-basin salt controlled basin (Bodego & Agirrezabala, 2013;Bodego, Iriarte, López-Horgue, & Álvarez, 2018); 5-7: Gaujacq and Ossun diapirs (Canérot et al, 2005); 6: Mauléon basin diapirs (Jammes et al, 2010); 8: Cotiella extensional salt area (McClay et al, 2004); 9: Sopeira and Sant Gervàs diapirs (Saura et al, 2016); 10: Villahermosa del Rio diapir (Canérot, 1991); 11: Parcent diapir (Pedrera et al, 2014); 12: Altea diapir (Pedrera et al, 2014;Martínez del Olmo et al, 2015); 13, 14: Finestrat and Elda diapirs (Martínez del Olmo et al, 2015); 15: Jumilla diapirs (Escosa et al, 2018); 16: Western Betics ; 17, 18: Faro and Albuferia diapirs (Ramos et al, 2016); 19, 20: Santa Cruz and Caldas da Rainha diapirs (Alves et al, 2003;Pena do Reis et al, 2017). Iberian Range AB: Aragoneses Branch; Iberian Range CB: Castillan Branch; PB: Parentis Basin; AB: Asturian Basin; AP: As Pontes Basin; ALZ: Asturoccidental-Leonese Zone; CZ: Cantabric Zone; CM: Cantabrian Mountain; CS: Central System; CCR: Catalan Coastal Range; GB: Guadalquivir Basin unconformities within the Jurassic and Lower Cretaceous successions were traditionally interpreted in terms of syn-rift to post-rift differential subsidence between fault-bounded tectonic domains (Aurell et al, 1992;Campos, Aurell, & Casas, 1996;Guimerà, 1988;Liesa, Soria, Meléndez, & Meléndez, 2006;Roca & Guimerà, 1992;Roca, Guimerà, & Salas, 1994;. The only previously documented examples of halokinesis within the Maestrat Basin are a diapir located in the Penyagolosa block near Villahermosa del Río village and in Lucena del Cid, north of Castelló (Canérot, 1989(Canérot, , 1991Trell, Canérot, & Martín, 1979) (see location in…”
mentioning
confidence: 99%
“…45 Polito et al undertook a retrospective review in 2018 of 110 paediatric patients using nabilone for CINV, primarily in conjunction with standard anti-emetic therapy (5HT3) for acute CINV. 46 They found that the proportion of patients obtaining a complete response to combined therapy was low (50.6% in moderate emetogenic chemotherapy and 53.8% in high emetogenic chemotherapy) and similar to previously described mono-therapy. 46 There has been interest in the use of cannabinoid-based medicines in other areas of nausea relief, specifically in the areas of radiotherapy and post-operative care.…”
Section: -16supporting
confidence: 84%
“…46 They found that the proportion of patients obtaining a complete response to combined therapy was low (50.6% in moderate emetogenic chemotherapy and 53.8% in high emetogenic chemotherapy) and similar to previously described mono-therapy. 46 There has been interest in the use of cannabinoid-based medicines in other areas of nausea relief, specifically in the areas of radiotherapy and post-operative care. Kleine-Brueggeney et al…”
Section: -16supporting
confidence: 84%
“…76 Currently, cannabinoids (nabilone, dronabinol) are considered as third or fourth line of choice, or as the last option in patients in which previous standard treatments do not achieve the desired effect. 31,37,43,47,[82][83][84][85] Unfortunately, a ratio of the effectiveness of cannabinoid compared to the effectiveness of conventional therapy is still unknown. Chronic use of cannabinoids can cause an excessive hyperemesis syndrome characterized by cyclic vomiting without any other recognizable reasons.…”
Section: Discussionmentioning
confidence: 99%